2015
DOI: 10.1097/md.0000000000001022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 23-Valent Pneumococcal Polysaccharide Vaccine Inoculated During Anti-Cancer Treatment Period in Elderly Lung Cancer Patients on Community-Acquired Pneumonia Hospitalization

Abstract: To evaluate effectiveness of 23-valent pneumococcal polysaccharide vaccine (PPSV23) inoculated during defined “vaccination period,” first 6 months post cancer diagnosis (ie, an anti-cancer treatment period), in elderly lung cancer patients on community-acquired pneumonia (CAP) hospitalization incidence.This was a nationwide population-based cohort study of 157 newly diagnosed elderly lung cancer patients receiving PPSV23 during “vaccination period”, and 628 age and sex one-to-one matched controls enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
(35 reference statements)
2
19
0
1
Order By: Relevance
“… 27 Our pneumonia study in patients with lung cancer conducted earlier in Taiwan showed that PPSV23 inoculated during the active anticancer treatment period could effectively reduce risk of hospitalised pneumonia. 13 In this study, our results confirmed that PPSV23 can protect elderly long-term cancer survivors against pneumonia. Because the cost of PPSV23 is low, it can be considered a feasible strategy for coping with the high risk of pneumonia in elderly cancer survivors.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“… 27 Our pneumonia study in patients with lung cancer conducted earlier in Taiwan showed that PPSV23 inoculated during the active anticancer treatment period could effectively reduce risk of hospitalised pneumonia. 13 In this study, our results confirmed that PPSV23 can protect elderly long-term cancer survivors against pneumonia. Because the cost of PPSV23 is low, it can be considered a feasible strategy for coping with the high risk of pneumonia in elderly cancer survivors.…”
Section: Discussionsupporting
confidence: 80%
“… 29 The study by Chiou et al reported a much higher incidence of 444 per 1000 PYs in patients with lung cancer aged ≥75 years, which they attributed to much older age, immunocompromised status during cancer treatment and poor pulmonary function. 13 In the present study, the incidence rate in long-term cancer survivors aged ≥75 years was 117.82 per 1000 PYs. These data highlight the importance of pneumonia vaccination in the elderly population.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Second, our study did not investigate whether pneumococcal vaccine (PSV 23 or PCV 13) was given. Chiou et al [34] noted that the cumulative hospitalization rate for pneumonia over two years in lung cancer patients was 37.1% in the vaccinated group and 55.4% in the non-vaccinated group. Third, exclusion of radiation pneumonitis was not complete because differential diagnosis between pneumonia and radiation pneumonia was based on retrospective medical chart and radiologic findings reviews.…”
Section: Discussionmentioning
confidence: 99%
“…In the article “Effect of 23-Valent Pneumococcal Polysaccharide Vaccine Inoculated During Anti-Cancer Treatment Period in Elderly Lung Cancer Patients on Community-Acquired Pneumonia Hospitalization: A Nationwide Population-Based Cohort Study”, 1 which appeared in Volume 94, Issue 26 of Medicine , an incorrect version of Figure 1 appeared. The article has since been corrected online.…”
mentioning
confidence: 99%